2015
DOI: 10.1371/journal.pgen.1005386
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Locus Harbouring a Functional CD164 Nonsense Mutation Identified in a Large Danish Family with Nonsyndromic Hearing Impairment

Abstract: Nonsyndromic hearing impairment (NSHI) is a highly heterogeneous condition with more than eighty known causative genes. However, in the clinical setting, a large number of NSHI families have unexplained etiology, suggesting that there are many more genes to be identified. In this study we used SNP-based linkage analysis and follow up microsatellite markers to identify a novel locus (DFNA66) on chromosome 6q15-21 (LOD 5.1) in a large Danish family with dominantly inherited NSHI. By locus specific capture and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…For example, a recent study identified a novel C-terminal truncating variant in CD164 that segregated with nonsyndromic hearing impairment in an affected family. Only the last six amino acids of CD164 were removed, but without the encoded canonical sorting motif, the truncated protein was trapped on the cell membrane (Nyegaard et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study identified a novel C-terminal truncating variant in CD164 that segregated with nonsyndromic hearing impairment in an affected family. Only the last six amino acids of CD164 were removed, but without the encoded canonical sorting motif, the truncated protein was trapped on the cell membrane (Nyegaard et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The stained samples were examined using a confocal laser scanning microscope (LSM 780, Zeiss, Jena, Germany) using 40× oil-immersion objective with a NA of 1.3 [74].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent study identified a novel Cterminal truncating variant in CD164 that segregated with nonsyndromic hearing impairment in an affected family. Only the last six amino acids of CD164 were removed, but without the encoded canonical sorting motif, the truncated protein was trapped on the cell membrane (Nyegaard et al 2015).…”
Section: Discussionmentioning
confidence: 99%